2022
DOI: 10.3389/fpsyg.2022.903919
|View full text |Cite
|
Sign up to set email alerts
|

Social Media-Based Collaborative Learning Effects on Student Performance/Learner Performance With Moderating Role of Academic Self-Efficacy

Abstract: Social media has always been described as the channel through which knowledge is transmitted between communities, students, and learners. This social media has been utilized by university students in a way to encourage collaborative learning and social interaction. This study explores the use of social media in the process of collaborative learning among university students in China using a survey method, a total of 583 students from different universities were surveyed in this study. Through this investigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…For example, a previous study indicated that social media has a significant association with customer attitude, subjective norms, and perceived behavioral control ( Ringim and Reni, 2019 ). Another research showed the influence of social media-based learning and collaboration on pre-service teachers’ self-efficacy to enhance their academic performance ( Liu et al, 2022 ). In our study, we established the association between the social media-based community of inquiry and the perceived behavioral control of the pre-service teachers for their intentions to implement equitable education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a previous study indicated that social media has a significant association with customer attitude, subjective norms, and perceived behavioral control ( Ringim and Reni, 2019 ). Another research showed the influence of social media-based learning and collaboration on pre-service teachers’ self-efficacy to enhance their academic performance ( Liu et al, 2022 ). In our study, we established the association between the social media-based community of inquiry and the perceived behavioral control of the pre-service teachers for their intentions to implement equitable education.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, social media use was found to have a positive relationship with subjective norms, perceived behavioral control, and the purchase intention of customers ( Sun and Xing, 2022 ). In their study, Liu et al (2022) concluded that social media played an essential role in increasing the perceived behavioral control (PBC) of its users concerning certain behaviors.…”
Section: Hypothesis Development and Conceptual Frameworkmentioning
confidence: 99%
“…Moreover, Qureshi et al (2021) suggested that engagement is critical for deep learning. Active engagement is a positive force for collaborative learning (Liu et al, 2022). Low-capacity members are prone to rely on high-capacity members to provide explanations; however, listening to these explanations involves only a low level of engagement.…”
Section: Effect Of Member and Group Working Memory Capacity On Hetero...mentioning
confidence: 99%
“…There have been few studies and viewpoints that have recognized four key benefits of using social media in higher education. These include strengthening connections, boosting the desire for learning, providing tailored course content, and nurturing teamwork 3 . However, extensive use of social media is causing youths to suffer from different kinds of physical and mental disorders.…”
Section: Introductionmentioning
confidence: 99%